Cosmolaelaps Berlese (Mesostigmata: Laelapidae) from southern Brazil, with a new record of a heteromorphic male, description of a new species, and a key to the species reported from that country - Duarte, Adriane Da Fonseca; Moreira, Grazielle Furtado; Cunha, Uemerson Silva Da; Moraes, Gilberto José De (Zootaxa, 2017)
Three Cosmolaelaps species were found in surveys recently conducted in the Pampa biome in southern Brazil. One of these is a new species here described as Cosmolaelaps pampaensis sp. nov. In the same surveys, heteromorphic male specimens of Cosmolaelaps guttulatus (Karg, 1978) were collected. A key for the identification of species of Cosmolaelaps reported from Brazil is provided.